Sosialisasi dan Pelatihan Permainan Digital EmoGame untuk meningkatkan kognitif lansia di Werdha Dharma Bakti Sumatera Selatan - damayanti, nita rosa; Ali, Nazlena Mohamad; Antoni, Darius (Jurnal Nasional Pengabdian Masyarakat, 2025)
EmoGame is a cognitive and emotional game that is useful for helping the elderly with Mild Cognitive Impairment (MCI). EmoGame was developed with a memory therapy approach. This therapy can help cognitive and positive emotions and introduce objects through images, such as images of old objects and old music in old age. This study aims to build a game application for the elderly with MCI on the Android platform to support the improvement of cognitive abilities and positive emotions in the elderly. This application has two games, namely memory puzzles and memory exploration. with the socialization and training at Werdha Dharma Bakti South Sumatra, it is hoped that this EMogame application can be used for the elderly who have experienced cognitive disorders to always practice memory recall. with training using this EMoGame application, we hope that the health of the elderly's memory will be slow to decline so that the elderly will always live healthily.